Huntington Mice Demonstrate Diminished Pain Response in Inflammatory Pain Model. (February 2018) - Lin, Ya-Chi; Hsiao, Hung-Tsung; Wu, Sheng-Nan; Liu, Yen-Chin
Abstract : BACKGROUND: Huntington disease (HD) affects the nervous system and leads to mental and motor dysfunction. Previous studies have shown that HD is caused by the exon 1 region of the huntingtin (HTT) gene having expanded CAG trinucleotide repeats. However, few studies have focused on the relationship between HD and pain. The purpose of this study is to investigate the relationship between HD and pain response. METHODS: We used clinical similar transgenic HD mice carrying a mutant HTT exon 1 containing 84 CAG trinucleotide repeats to evaluate the relationship between HD and pain. Inflammatory pain models were induced by either formalin or complete Freund adjuvant injection over the hind paw. Spinal cord, dorsal root ganglion, and paw skin tissues were harvested at the end of the behavioral inflammatory pain studies. Immunofluorescence assay, Western blotting, and enzyme-linked immunosorbent assay were used to identify changes in cells and cytokines. RESULTS: Our data demonstrate that preonset HD mice exhibited less pain behavior than wild-type (WT) mice in both young (n = 11 [WT], 13 [HD]) and aged (n = 8 [WT], 9 [HD]) mice. Western blotting and immunohistological examination of lumbar spinal cord tissue and dorsal root ganglion indicate less activation of glial cells and astrocytes in young HD mice (n = 6–7) compared to that in WT mice (n = 6–7). The production levels of tumor necrosis factor-α, interleukin-1β, and substance P were also lower in young HD mice (n = 6–7). CONCLUSIONS: Our data demonstrate less pain behavior and pain-related cytokine response at the spinal cord level for HD mice compared to those for WT mice. Further studies are needed for determining the mechanism as to how mutant HTT leads to altered pain behavior and pain-related cytokine response. Abstract : Published ahead of print August 30, 2017.